Adiabatic magnesium hydride system for hydrogen storage based on thermochemical heat storage: Numerical analysis of the dehydrogenation. (15th February 2019) - Lutz, Michael; Bhouri, Maha; Linder, Marc; Bürger, Inga
Graphical abstract: Highlights: Hydrogen release from a novel storage reactor with high capacities at low pressures. Coupled magnesium hydride dehydrogenation and magnesium oxide hydration feasible. Water vapor supply to the storage reactor at 10 bar and 350 °C possible. Dehydrogenation rate dependent on the vapor supply-pressure. Magnesium hydride dehydrogenation reaction fast enough for stationary applications. Abstract: With hydrogen becoming more and more important as storage and carrier for renewable energy, there is an increasing need for flexible and efficient storage technologies. However, existing technologies, such as liquefaction or compression, often require a significant share of the hydrogens lower heating value. High-temperature metal hydrides (HT-MHs), such as magnesium hydride, are a promising alternative. Due to high operation temperatures, their application is challenging. A novel adiabatic hydrogen storage reactor based on the combination of a HT-MH with a thermochemical energy storage system (TCSS), such as Mg(OH)2 /MgO + H2 O, can be a solution. In this work, the previously published numerical simulations for hydrogen absorption are extended to the desorption process. A two-dimensional model for the hydrogen release was set up. The performance of the storage reactor is strongly dependent on the thermodynamic equilibrium of the reactions involved and less dependent on the reaction kinetics. Dehydrogenation is possible within 132 min, which is in the vicinity of the hydrogenation time. To enhance the dehydrogenation process, the water vapor pressure can be adjusted aiming for higher temperatures during the MgO hydration. Hydrogen can either be provided at constant pressure or constant mass flow rate.